Oil Production And Host Community Relations In Nigeria: The Limits Of The Utilitarian Approach - Ayotunde, Lola (Journal of Sustainable Development Law and Policy, 2025)
While resource extraction generates enormous revenue for resource-rich countries such as Nigeria, it could also engender human rights violations in host communities. This article explores the efficacy of the prevailing utilitarian approach to oil and gas management in Nigeria. The utilitarian calculus is applied to Nigeria’s oil and gas management to demonstrate how the utilitarian theory substantially influences the decisions of the Nigerian government. Although utilitarianism posits that the happiness of the majority is the primary objective of governance, this is arguably not a viable reason to violate the rights of the minority Niger Delta communities for the economic gains of the majority of Nigerians. As an alternative to the ineffective and unsustainable utilitarian resource management approach, this article discusses the importance of the human rights-based approach to resource management.